Research developments and applications of ice slurry - Song, Haiqin; Verdin, Patrick G.; Zhang, Jinfeng (MDPI, 2024)
Ice slurry is a phase-changing material composed of liquid water, ice crystals, and a freezing point depressant. It is finer and more uniform compared to ice cubes or flake ices and is used in many industries, such as food preservation, comfortable cooling, medical protective cooling, sport cooling, instrument cooling, firefighting, and artificial snowmaking, due to its high energy storage density. Ice slurry with high concentration can be used for cleaning equipment as its friction is several times greater than that of water at the same flow rate. This paper describes in detail the developments of ice slurry, including production methods, concentration measurement approaches, flow and heat transfer characteristics, as well as its applications in various industries. Problems to be solved or improved are also discussed, providing suggestions for better developments and applications in industrial environments.
Keywords: 40 Engineering; 33 Built environment and design; 51 Physical sciences; ice slurry; production methods; concentration measurement approaches; flow and heat transfer characteristics; applications